Digital Literacy 2013
DOI: 10.4018/978-1-4666-1852-7.ch042
|View full text |Cite
|
Sign up to set email alerts
|

Gender Digital Divide and National ICT Policies in Africa

Abstract: The chapter provides an examination of the concept of the digital divide in Africa and its effect on the women in Africa, how ICTs can be used as tools for gender equality and empowerment and the barriers women face in regards to access to ICT infrastructure. These barriers includes: lack of access to physical infrastructure, illiteracy, social and cultural limitations, lack of finance, decision making ability, segregation in employment issues, etc. Also examined is the historical development of ICT policies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This is so because the Internet found either inside the physical or virtual library is very useful to university students' especially in Nigeria because it enables them to have access to timely, accurate and relevant information that cannot be obtained from library shelves. In consonance with the finding, Ikolo and Okiyi (2013) noted that Internet search helps university students to boost their intellectual development and job preparation. However, this may not be possible without the students' information search knowledge.…”
Section: Knowledge Of Information Sourcing and The Use Of Library By ...supporting
confidence: 53%
See 1 more Smart Citation
“…This is so because the Internet found either inside the physical or virtual library is very useful to university students' especially in Nigeria because it enables them to have access to timely, accurate and relevant information that cannot be obtained from library shelves. In consonance with the finding, Ikolo and Okiyi (2013) noted that Internet search helps university students to boost their intellectual development and job preparation. However, this may not be possible without the students' information search knowledge.…”
Section: Knowledge Of Information Sourcing and The Use Of Library By ...supporting
confidence: 53%
“…The Internet is very useful to university students' especially in Nigeria because it enables them to have access to timely, accurate and relevant information that cannot be obtained from library shelves. Ikolo and Okiyi (2013) noted that Internet searching helps university students to boost their intellectual development and job preparation. However, this may not be possible without the students' information search knowledge which can be developed by all students who make use of the school library regardless of whether they are rich or poor.…”
mentioning
confidence: 99%
“…Earlier studies identified limited access to physical infrastructure, illiteracy, social and cultural limitations, a lack of finance (affordability), lack of decision-making ability and segregation in employment as some of the barriers to women's adoption of digital technologies in Africa (Aikins, 2019;Ikolo, 2013). The importance of digital technologies for manufacturing, skills development, research and development, integration and intra-African trade, investment and tourism requires that policymakers pay particular attention to these sociocultural, economic and institutional factors that contribute to the gender-based digital divide at firm level on the African continent (African Union Commission, 2015).…”
Section: Estimates Of Digital Technology Adoption and Utilisationmentioning
confidence: 99%
“…It may affect the ability of women-owned businesses to readily adapt to e-commerce platforms, which are increasingly adopted because of containment measurements related to the COVID-19 disease (Mastercard, 2020). Digital technologies can be used not only to support best practice but also as a tool to promote gender equality and empowerment of women, by enhancing their employment opportunities and increasing their access to knowledge and general information (Ikolo, 2013;OECD, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation